A quota-based GHG emissions quantification model for the construction of subway stations in China. (10th October 2018) - Liu, Minghui; Jia, Siyi; He, Xiaotong
Abstract: Subway construction in China has experienced a surge during the past decade. Though subway is often viewed as a clean commute mode, the construction of its stations and tunnel sections requires large quantities of energy consumption, generating multiple pollutants, among which the Green-house gas (GHG) emissions would be a major issue in the context of a worldwide plea for carbon reduction, and it has to be quantified for the interest of a comprehensive assessment with regard to the GHG emissions of subway system. This paper proposed a GHG emissions quantification model for the construction of the subway stations based on a quota. A quota-based GHG emissions quantification model is able to estimate GHG emissions during the planning stage of subway projects, providing designers with the environmental consciousness on their design choices, as well as a reference for reduction potential of GHG emissions within or among schemes. Specifically, GHG emissions in the construction of subway stations are attributed to the contribution of each sub-project, a database for the GHG emissions of those sub projects is established through their construction quota. Case study for an open-excavation station shows 69% of the GHG emissions come from the construction of main structures. In terms of emission sources, embodied emissions account for 90.72% of the totality, of which concrete and steel components are the two major contributors. Besides, parameter on the buried depth of top slab shows that GHG emissions from each sub-projects increase with buried depth.